Trigeminal neuralgia: treatment modalities and clinical results, a retrospective study of 101 cases - CHAHBAR Abdelaziz (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2020)
Over a period of 25 years, from 1993 to 2018, 101 patients of a mean age of 55,93 years, suffering from classical trigeminal neuralgia, underwent different types of surgical treatments at the neurosurgery department of Hôpital des spécialités ONO in Rabat, the aim of this study is to evaluate and compare the efficacy of these surgical treatments in both short-term (3 months) and mid-term (1 to 2 years). The choice of a certain technique depends on many factors: the age of the patient and its general condition (ASA score), the consent of the patient and the decision of the medical staff. The efficacy of each technique is evaluated at short-term by existence of an immediate pain relief as well as the complications rate, the mid-term outcome is evaluated using the complete pain relief and the recurrence rate criteria. In our study, all surgical techniques are highly effective either at the short or the mid-terms, leading to good pain control, however, there are slight differences in terms of safety, simplicity and efficacy between this spectrum of surgical techniques. Concerning the immediate pain relief, percutaneous techniques, mainly, the radiofrequency thermocoagulation, presents the highest rate of immediate pain relief (97,7%). Microvascular decompression, considered in literature as the gold standard operation, presented the lowest complications rate (34,61%), the best mid-term pain control (76,92%) and the lowest recurrence rate (15,38%) versus the percutaneous techniques, making it the ideal technique to be applied if patient meets the operability criteria. It is necessary to continue studies on a larger patients' selection and a longer period to improve outcomes reliability on defining the best choice
Keywords: Follow-up; Gamma Knife radiosurgery; Microvascular decompression; Percutaneous balloon compression, Radiofrequency thermocoagulation; Trigeminal neuralgia